0375 Mortality of a cohort of workers in Great Britain with blood lead measurements. (23rd June 2014) - McElvenny, Damien; Miller, Brian; MacCalman, Laura; Sleeuwenhoek, Anne; van Tongeren, Martie; Shepherd, Kevin; Darnton, Andrew; Cherrie, John
Abstract : Objectives: We report on the first ever analysis of a UK cohort of workers with blood lead level measurements that was assembled in the late 1970s. Method: As an alternative to mean and maximum blood lead levels, we carried out an exposure assessment that assigned workers to high, medium or low exposure to lead. We additionally assessed whether workers would be exposed to an important level of relevant co-carcinogens. Results: 3466 deaths were observed among 7770 men and 1352 women. The SMRs for all causes (109, 95% CI 105–112) and all malignant neoplasms (113, 107–120) were significantly raised. SMRs for oesophageal, stomach, bladder, brain and kidney cancer and non-malignant kidney disease were not raised, but were raised for lung cancer (142, 129–157). The SMR for circulatory diseases (105, 99–100) was of borderline significance. No trends were observed for mean or maximum blood lead level or assessed lead exposure for any of the cancers of a priori interest, but a significant association was found for circulatory diseases (ischaemic heart disease) with mean and maximum blood lead level. Conclusions: The excess of lung cancer is possibly to be due to tobacco smoking. This study provides strong evidence to support an association between increased lead exposure and increased risk of ischaemic heart disease mortality. The study is, however, limited by the lack of complete occupational histories for the included participants.